Reduksi Gaya Drag Silinder Sirkular dengan Penambahan Square Disturbance Body Melalui Simulasi Numerik 2D Unsteady-RANS pada Reynolds Number 34800 - Rina Rina; Ruzita Sumiati; Adriansyah Adriansyah (METAL: Jurnal Sistem Mekanik dan Termal, 2018)
Circular cylinder has a strong  adverse pressure gradient. When a fluid flows around the circular cylinder, it will produce aerodynamics force. One of them is  the drag force which strong enough. Hence, control of flow need to reduce the drag force with placed a disturbance body on the upstream side. The purpose of this study is to compare and complement the experimental research of drag reduction that has been done before. The aerodynamics characteristics of the disturbance body and cylinder are modelled in two dimensions Unsteady-RANS by using fluent with turbulent flow. It is found that the mean drag and the lift fluctuation of the cylinder can be reduced by the upstream disturbance body with the s/D = 0.107 (here s and D are side length of the disturbance body and the diameter of cylinder, respectively). The position of the disturbance body is varied at (α) 20º, 30º, 40º, 50º and 60º with a gap distance (δ = 0.4mm). Reynolds number based on cylinder diameter ReD = 3.48x104. Fluid interaction between circular cylinder with two disturbance body can increase boundary layer transition from laminer to turbulent to produce small drag. It is found that the characteristics of the flow significantly depend on the position of disturbance body. The optimum condition for the drag force reduction is at the angle α = 30º  about  53 %.